2010
DOI: 10.4161/viru.1.4.12004
|View full text |Cite
|
Sign up to set email alerts
|

Examination of maternal gingival crevicular fluid for the presence of selected periodontopathogens implicated in the pre-term delivery of low birthweight infants

Abstract: Association of bacterial species with the risk of periodontal disease and thus the risk of preterm delivery was only observed when they occurred in pairs or groups of three or more. Aa appeared to be a necessary co-factor for significant associations of bacterial groups with the variables recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
1
13
0
2
Order By: Relevance
“…In other cases where periodontal disease was evident 15,26 and members of the Red and Orange complexes were detected in subgingival plaque 15,99 or gingival crevicular fluid, 26 no differences between PTB and FTB were found, nor were any Red complex bacteria detected in the absence of the Orange complex in any of these studies, confirming that colonization of the Orange complex is a prerequisite for the Red complex to become established.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…In other cases where periodontal disease was evident 15,26 and members of the Red and Orange complexes were detected in subgingival plaque 15,99 or gingival crevicular fluid, 26 no differences between PTB and FTB were found, nor were any Red complex bacteria detected in the absence of the Orange complex in any of these studies, confirming that colonization of the Orange complex is a prerequisite for the Red complex to become established.…”
mentioning
confidence: 49%
“…Examples are P. gingivalis, T. denticola, T. forsythia, F. nucleatum, Aa and Campylobacter, [200][201][202][203] resulting in the production of excessive inflammatory responses. periodontal disease in pregnant women in an effort to prevent adverse pregnancy outcomes, while recent studies have indicated that the BANA test may be a useful screening tool in identifying mothers at risk for PTB 13,26,73 and would be worth exploring. It is reasonable to suggest that infection of the gingiva and periodontium by Gram-negative anaerobic bacteria provide a reservoir for microbial products (e.g., LPS) and sufficiently challenge the host to produce responses which may be deleterious to both the pregnant mother and the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todavia, este resultado deve ser interpretado com cautela, em virtude do amplo intervalo de confiança identificado (95% IC: 1,21 a 93,34). A influência clínica dos periopatógenos originados de bolsas periodontais na prematuridade permanece questionável, uma vez que outros estudos têm falhado em mostrar tal associação 13,28 . A freqüência do Aa apresentou-se elevada na amostra analisada (57,5%), corroborando com outros achados 28 que também relataram uma alta prevalência (45%) desta bactéria em um estudo envolvendo mães de bebês prematuros e ou baixo peso ao nascer.…”
Section: Resultsunclassified
“…A influência clínica dos periopatógenos originados de bolsas periodontais na prematuridade permanece questionável, uma vez que outros estudos têm falhado em mostrar tal associação 13,28 . A freqüência do Aa apresentou-se elevada na amostra analisada (57,5%), corroborando com outros achados 28 que também relataram uma alta prevalência (45%) desta bactéria em um estudo envolvendo mães de bebês prematuros e ou baixo peso ao nascer. Entretanto, esta freqüência se mostrou mais alta que a demonstrada em outros estudos envolvendo gestantes 4,21 , sugerindo uma maior ocorrência destas bactérias na amostra estudada e levando a questionar que fatores poderiam estar relacionados à maior frequência destas bactérias em gestantes, uma vez que o Aa, em geral, não se apresenta com alta prevalência em populações com gengivite e periodontite leve a moderada.…”
Section: Resultsunclassified